CLINICAL AND PHENOTYPIC FEATURES OF STROKE IN WORKERS EXPOSED TO AEROSOLS WITH PREDOMINANTLY FIBROGENIC EFFECTS - Яшникова, Мария Викторовна; Потеряева, Елена Леонидовна; Максимов, Владимир Николаевич (Medicine in Kuzbass, 2025)
The aim of the research – study of the characteristics of the course of stroke in men under conditions of exposure to aerosols of predominantly fibrogenic action study of the characteristics of the course of stroke in men under conditions of exposure to aerosols of predominantly fibrogenic action.Material and methods. We examined 121 men with stroke aged from 30 to 65 years, with work experience of 5 years or more, divided into two groups: the main group and the comparison group. The main group – 45 men who worked under conditions of exposure to aerosols of predominantly fibrogenic action in the professions: gas-electric welder, gas welder, smelter (class of working conditions – 3.1).The comparison group consisted of 76 men who were not exposed to harmful production factors at work. Both groups are comparable in age and work experience. The frequency of occurrence of cardiovascular factors and the dynamics of neurological deficit (NIHSS 1 and 2 scale) in the acute period of stroke were studied. Statistical processing of the obtained data was carried out according to generally accepted methods.Results. In the main group of stroke patients, middle-aged people were more common – 51.1%, but young people slightly predominated in the main group - 13.4% (in the comparison group – 11.8%, p > 0.05). Ischemic stroke prevailed – 90.1%, and among its subtypes – cardioembolic (main group – 12.8%, comparison group – 9.8%, p > 0.05). Hypertension was diagnosed in 100.0% in both groups, and the factor of smoking and alcohol abuse, the factor of the presence of coronary artery disease significantly prevailed in the main group. Men in the main group, regardless of age, had a pronounced neurological deficit according to the NIHSS scale after the acute period of stroke. In the main group, significant correlations were established between the level of total cholesterol, indicators of the NIHSS 1, NIHSS 2 scales and work experience.Conclusions. The phenotypic features of stroke in patients who worked under conditions of exposure to aerosols of predominantly fibrogenic action were established: the predominance of young people, the cardioembolic subtype of ischemic stroke; high incidence of smoking and alcohol abuse factors, ischemic heart disease factors; severe stroke in the group as a whole and in each age group.Limitations. The following were excluded from this study: female gender, age less than 30 and more than 65 years, the diagnosis of «transient cerebrovascular accident», work experience less than 5 years, the presence of acute infectious diseases.Ethics. The study was carried out in compliance with the «Ethical principles of scientific medical research involving humans» and «Rules of clinical practice in the Russian Federation», approved by the Order of the Ministry of Health of the Russian Federation dated June 19, 2003 No. 266; approved by the local ethics committee at the Federal State Budgetary Educational Institution of Higher Education of the National State Medical University of the Ministry of Health of Russia
Keywords: stroke; men; aerosols of predominantly fibrogenic action; risk factors for stroke